A coupled hygro-thermo-mechanical model for concrete subjected to variable environmental conditions. (August 2016) - Gasch, Tobias; Malm, Richard; Ansell, Anders
Abstract: It is necessary to consider coupled analysis methods for a simulation to accurately predict the long-term deformations of concrete structures. Among other physical fields that can be considered, both temperature and moisture have a significant influence on the deformations. Variations of these fields must therefore be included implicitly in an analysis. This paper presents a coupled hygro-thermo-mechanical model for hardened concrete based on the framework of the Microprestress–Solidification theory. The model accounts for important features of concrete such as ageing, creep, shrinkage, thermal dilation and cracking; all of these under variable temperatures and moisture conditions. It is discussed how to implement the proposed model in a flexible numerical framework that is especially suitable for multi-physics analyses. The capabilities of the model are shown through the analysis of three experimental data sets from the literature, with focus on creep and shrinkage. Overall, the agreement between the analysis and experimental results is good. Finally, a numerical example of a concrete gravity dam with dimensions and loads typical to northern Sweden is analysed to show the capabilities of the model on a structural scale.